Re-thinking Renaissance objects - Motture, Peta; O'Malley, Michelle (Renaissance studies special issues, 2011)
"Re-thinking Renaissance objects considers key issues at the heart of current scholarly debate on Renaissance art and culture. Inspired by research that has developed from the redisplay of the outstanding Medieval and Renaissance collections at the Victoria and Albert Museum, the authors use the objects themselves as their starting point in their papers. The book explores and often challenges assumptions about the interconnection between sacred and secular belief, the problems inherent in making distinctions between 'artists' and 'artisans', and the various ways in which ideas were exchanged across media and cultural boundaries. This object-based approach has often helped revolutionize our thinking not only about individual pieces but also about the culture for which these works were created. The volume brings together V&A curators with other experts. The result is an impressive range of contributions which build on a wealth of existing scholarship in order to cast new light on the appearance, meaning, style and function of a collection of Renaissance artistic works"--